2006
DOI: 10.1196/annals.1386.025
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Remodeling and Control of Cell Proliferation by Progestins via Cross Talk of Progesterone Receptor with the Estrogen Receptors and Kinase Signaling Pathways

Abstract: Transcription from the mouse mammary tumor virus (MMTV) promoter can be induced by glucocorticoids or progestins. Progesterone treatment of cultured cells carrying an integrated single copy of an MMTV transgene leads to recruitment of progesterone receptor (PR), SWI/SNF, and SNF2h-related complexes to MMTV promoter. Recruitment is accompanied by selective displacement of histones H2A and H2B from the nucleosome B. In nucleosomes assembled on promoter sequences, SWI/SNF displaces histones H2A and H2B from MMTV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
(92 reference statements)
2
27
0
1
Order By: Relevance
“…The MMTV promoter contained in its 5Ј long terminal repeat has been extensively studied and has become the model for progesterone-and glucocorticoid-induced gene expression in human breast cancer cell lines (17,63). Using this model, we have recently contributed to connecting the rapid signaling activation by progesterone with its transcriptional effect (62).…”
Section: Discussionmentioning
confidence: 99%
“…The MMTV promoter contained in its 5Ј long terminal repeat has been extensively studied and has become the model for progesterone-and glucocorticoid-induced gene expression in human breast cancer cell lines (17,63). Using this model, we have recently contributed to connecting the rapid signaling activation by progesterone with its transcriptional effect (62).…”
Section: Discussionmentioning
confidence: 99%
“…Semiquantitative footprinting and filter binding studies indicated that receptors bound at all four of the PREs, [2][3][4] and glycerol gradient centrifugation studies 4 suggested that dimers assembled at each site. 5 Finally, mutational studies indicated that loss of any one site decreased the level of transcriptional activity up to 10-fold, 6 demonstrating that transcriptional activation was synergistic in character and, thus, suggestive of communication among the sites.…”
Section: Introductionmentioning
confidence: 97%
“…Initial studies focused on the role of histone acetylation and, to a lesser extent, on histone phosphorylation and histone arginine methylation (Bartsch et al 1996;Spencer et al 1997;Li et al 2003;Metivier et al 2003;Vicent et al 2006b), while lysine methylation has not been studied extensively (Metzger et al 2005;Wissmann et al 2007). Although H3 trimethylated at Lys 4 (H3K4me3) is associated with transcription start sites (TSSs) of active genes (Santos-Rosa et al 2002, 2003Schneider et al 2004), the role of this modification during mouse mammary tumor virus (MMTV) activation has been questioned (Kinyamu and Archer 2007).…”
mentioning
confidence: 99%